Basics of polymers : fabrication and processing technology - Muralisrinivasan, Natamai Subramanian (New York, [New York] (222 East 46th Street, New York, NY 10017) : Momentum Press, 2015)
This book constitutes one of the most important aspects of polymer processing and technology. The performance of polymers is evolving the most rapid increasing volume of production. Polymers are an important commodity in the modern lifestyle. Polymers are undoubtedly superior materials in terms of their costs, processability, and functional properties. The fabrication and processing technology is showing higher growth than the number of polymer grades in the market.
1. Introduction -- 2. Principles of polymers and polymerization -- 3. Polymer structure and property -- 4. Polymer materials and their processing -- 5. Polymer processing technology -- 6. Injection molding -- 7. Extrusion -- 8. Blow molding -- 9. Rotational molding -- 10. Thermoforming -- 11. Research on polymer processing -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF title page (viewed on June 12, 2015).
Keywords: Polymers; amorphous; anionic polymerization; morphology; processing; molecular weight; polymer properties; crystalline; polyethylene; polypropylene; acrylonitrile-butadiene-styrene; nylon; polycarbonate; stress relaxation; injection molding; extrusion; thermoforming; rotational molding; compounding; melt flow rate; thermomechanical; melting point; screw extrusion; hollow parts; research; process simulation